2009
DOI: 10.1093/ejechocard/jep169
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular remodelling in pulmonary arterial hypertension with three-dimensional echocardiography: comparison with cardiac magnetic resonance imaging

Abstract: RV remodelling in PAH patients can be accurately assessed with both 3DE and CMR. Both modalities are robust and reproducible with CMR being more reproducible for measurements of EF and RV mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 29 publications
2
93
0
3
Order By: Relevance
“…124 In adults with PAH, good correlation was found in the calculation of RVEF and RVEDV determined by either 3D echocardiography or MRI measurements. 125 It was recently shown that adult patients with some forms of PH had more dilated, hypertrophied, and poorly functioning RVs than adults with other forms. 126 The use of 3D echocardiography has been validated for the measurement of RV volumes and EF, which correlated well with those variables determined by MRI imaging in a pediatric population.…”
Section: D Echocardiographymentioning
confidence: 99%
“…124 In adults with PAH, good correlation was found in the calculation of RVEF and RVEDV determined by either 3D echocardiography or MRI measurements. 125 It was recently shown that adult patients with some forms of PH had more dilated, hypertrophied, and poorly functioning RVs than adults with other forms. 126 The use of 3D echocardiography has been validated for the measurement of RV volumes and EF, which correlated well with those variables determined by MRI imaging in a pediatric population.…”
Section: D Echocardiographymentioning
confidence: 99%
“…Relatively new and not fully explored areas include clinical significance of tricuspid plane motion dynamics [66,67], three-dimensional echocardiography of the right heart [26,75] and modern methods of local RV strain rate assessment [69,70]. While a few of them increase the quality of individual patient evaluation [68], others mostly prolong an already extensive list of measurements, which are currently being taken during a resting echocardiographic examination aimed at diagnosing, staging or following up PH.…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, although standard 2D transthoracic echocardiography has provided merely 3 potential treatment goals-preserved tricuspid annulus systolic excursion, normal right atrial area, and the absence of pericardial effusion-modern right heart echocardiography has potentially more to offer. [10][11][12][13][14][15][16][17][18][19][20] Of note, in their study, Ryo et al did not follow this direction but limited the assessment to rather rudimental estimation of RV volumes, simply expecting better precision of the measurements assisted by 3D wall motion tracking when compared with traditional 2D echocardiography. Similar to CMR, this still required manual tracing of endocardial and epicardial borders.…”
Section: See Article By Ryo Et Almentioning
confidence: 95%